Pelatihan Keterampilan Sosial untuk Menurunkan Perilaku Agresif Anak - Dwi Nikmah Puspitasari (University of Merdeka Malang, 2014)
Social skill training aims to lower or reduce the aggressive behavior of children who are in the village UPTD Children Affairs. The method used in this study was a quantitative experimental methods and design of pre-experimental one group pretest-posttest. Analysis of the data in this study used t-test. This study used a total of 11 samples were selected using purposive sampling technique. Means of data collection in this study was the scale of aggressive behavior is a form of translation of the Aggression Questionnaire Western Psychological Services (WPS) Test Report with r = 0.730, and social skills training module which is a form of translation of the Social Skills Training for Adolescents with General Moderate Learning Difficulties. From the results of statistical tests known that social skills training is not effectively used to reduce the aggressive behavior of children who are in the village UPTD Children Affairs.